Optimalisasi ZISWAF dalam Meningkatkan Kesejahteraan Pesantren: Studi Kasus di Pesantren Quran elTAHFIDH Indonesia - Muhammad Ulul Albab Alfirdaus; Bayu Taufiq Possumah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study examines the development and potential of zakat, infak, sedekah, waqf (ZISWAF) in improving the welfare of Islamic boarding schools, with a case study at the elTAHFIDH Indonesian Quran Boarding School. Using a qualitative method with a triangulation approach through in-depth interviews and Focus Group Discussions (FGD), this study found that the ZISWAF program has an important role in improving the welfare of Islamic boarding schools. Before the ZISWAF program, Islamic boarding schools faced challenges such as limited capital financing, infrastructure preparation, and human resource financing. Through transparent and effective ZISWAF management, Islamic boarding schools have succeeded in improving welfare by building community trust, utilizing funds according to contracts, and routine reporting to donors. ZISWAF funds have a positive impact in various aspects, such as improving the quality of education, Islamic boarding school facilities, and the welfare of students and Islamic boarding school managers. Collaboration, transparency, and professionalism in managing ZISWAF funds are the keys to success in optimizing the potential of ZISWAF for the welfare of Islamic boarding schools.